(untitled) (Jurnal Ipteks Terapan, 2024)
Background: Fatigue is the most common symptom experienced by children with cancer, which can be caused by the disease and side effects of treatment, around 70-80% of child cancer patients undergoing treatment experience fatigue , several studies show that technology-based interventions are effective in reducing fatigue in children with cancer, but research in this area is still limited. Objective: This study aims to identify the benefits of Technology Based Intervention in reducing fatigue in children with cancer. Methodology: The method used in this research is a systematic review in accordance with PRISMA. The initial step taken is to determine the PICO, then search for and identify research that meets the objectives. The literature search used 7 databases, namely ProQuest, Clinicalkey For Nursing, Pubmed, Science Direct, Scopus, Embase, Sage Journal , articles in English and published from 2013-2023, then a review was carried out to evaluate the quality of the study using the Joanna Briggs Institute (JBI) form Results: a total of 8 articles met the inclusion criteria, consisting of 6 with an RCT design, 1 quasi- experimental design and 1 single group design . The results obtained were Technology Based Interventions that were effective in reducing fatigue , namely mobile applications, games, use of telehealth , and use of multimedia. Conclusion: Technology Based Intervention can reduce fatigue scores , in its application it can be combined with interventions that are not technology based